Augmented Reality in Computer Science: A Bibliometric Analysis - Loso Judijanto (Westscience Press, 2026)
This study examines the development and intellectual structure of augmented reality research within the field of computer science through a bibliometric approach. Data were collected from the Scopus database using relevant keywords and analyzed using VOSviewer and Biblioshiny. The analysis focuses on publication trends, influential authors and sources, collaboration networks, and keyword co-occurrence patterns. The results indicate that augmented reality occupies a central position in the research landscape, closely connected with core technological domains such as computer vision, computer graphics, and human–computer interaction. At the same time, the findings reveal a clear shift from technology-driven studies toward application-oriented research, particularly in education and healthcare. Density and overlay visualizations further highlight the emergence of topics related to e-learning, simulation, and user-centered design in recent years. These findings suggest that augmented reality research is evolving into a more interdisciplinary and context-driven field. This study contributes by providing a comprehensive mapping of research trends and identifying potential directions for future studies, particularly in integrating augmented reality with intelligent systems and domain-specific applications.